2022
DOI: 10.1021/acsami.2c07545
|View full text |Cite
|
Sign up to set email alerts
|

Improved Energy Storage Property of Sandwich-Structured Poly(vinylidene fluoride)-Based Composites by Introducing Na0.5Bi0.5TiO3@TiO2 Whiskers

Abstract: In recent years, high-energy-density polymer-based capacitors have received extensive attention because of their potential applications in advanced power systems and electronic equipment. However, their development is severely hampered by the inherent features of polymers such as low polarization and low charge–discharge efficiency (η). In this study, a new strategy for core–shell Na0.5Bi0.5TiO3(NBT)@TiO2(TO) whiskers combined with sandwich-structured poly­(vinylidene fluoride) (PVDF)-based dielectric composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The 0.2 wt% BFO@AO composite film reported in this work exhibited a high U d of 31.3 J cm −3 , which is the best when compared to previous references. 13,34–36…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 0.2 wt% BFO@AO composite film reported in this work exhibited a high U d of 31.3 J cm −3 , which is the best when compared to previous references. 13,34–36…”
Section: Resultsmentioning
confidence: 99%
“…The 0.2 wt% BFO@AO composite film reported in this work exhibited a high U d of 31.3 J cm À3 , which is the best when compared to previous references. 13,[34][35][36] Continuous and frequent charging and discharging processes will constantly generate heat, and the coupling effect of heat, electricity, and force seriously reduces the quality of the film, which is fatal to practical applications. Cyclic charge-discharge tests were performed to evaluate the reliability of the CRC-based nanocomposite films at 200 MV m À1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8. 19,28,33,37,[39][40][41][42][43][44][45][46][47][48][49] It can be seen that the sandwich-structured 0-0.6-0 nanocomposite reported in this work not only has a higher E b (B565 MV m À1 ), but also has a higher U d (B21.39 J cm À3 ) and Z (B70.54%), showing significantly better properties than other multi-layer nanocomposites. The results show that sandwich-structured nanocomposites are a convenient strategy to enhance the energy storage performance of composites.…”
Section: Energy Storage Performance and Leakage Current Distributionmentioning
confidence: 90%
“…10 (iv) The CS shell with moderate e r employed as a buffer layer can further reduce the e r -mismatch between BaTiO 3 and PP and alleviate the local electric field distortion at heterogeneous interfaces in composites. 22 (v) The positively charged CS shell exhibits an inherent high electron affinity, which introduces a number of charge traps into the composite dielectrics. These traps could capture free charges and suppress the fast development of an electrical tree, thus enhancing the E b of the composites.…”
Section: Breakdown Strength and Energy Storage Performances Of Batio ...mentioning
confidence: 99%
“…[19][20][21] To deal with this problem, in recent decades, a number of composite dielectrics were prepared by incorporating various high-e r inorganic nanofillers into different polymer matrices, aiming to merge the superiorities of these different phases and to achieve synchronous improvement in both e r and E b in composite dielectrics. [22][23][24][25] However, due to the significant difference in e r between polymer matrices and high-e r ceramic fillers, the localized electric field at the heterogeneous interface would be re-distributed non-uniformly, resulting in the accumulation of charges at the interface and the occurrence of premature breakdown in composites. [26][27][28] In recent years, researchers have found that the dielectric properties of ceramic fillers are closely dependent on their crystal size.…”
Section: Introductionmentioning
confidence: 99%